Type I CRISPR-Cas targets endogenous genes and regulates virulence to evade mammalian host immunity - Li, Rongpeng (Cell Res, 2016)
Clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated (Cas) systems in bacteria and archaea provide adaptive immunity against invading foreign nucleic acids. Previous studies suggest that certain bacteria employ their Type II CRISPR-Cas systems to target their own genes, thus evading host immunity. However, whether other CRISPR-Cas systems have similar functions during bacterial invasion of host cells remains unknown. Here we identify a novel role for Type I CRISPR-Cas systems in evading host defenses in Pseudomonas aeruginosa strain UCBPP-PA14. The Type I CRISPR-Cas system of PA14 targets the mRNA of the bacterial quorum-sensing regulator LasR to dampen the recognition by toll-like receptor 4, thus diminishing the pro-inflammatory responses of the host in cell and mouse models. Mechanistically, this nuclease-mediated RNA degradation requires a “5′-GGN-3′” recognition motif in the target mRNA, and HD and DExD/H domains in Cas3 of the Type I CRISPR-Cas system. As LasR and Type I CRISPR-Cas systems are ubiquitously present in bacteria, our findings elucidate an important common mechanism underlying bacterial virulence.